Improving Menopause Preparation Knowledge by Utilizing Digital Health Literacy in Family Planning Villages - meinarisa, meinarisa; Nasution, Riska Amalya; Nurlinawati, Nurlinawati; Sari, Putri Irwanti; Mulyani, Sri (Sekolah Tinggi Ilmu Kesehatan Harapan Ibu Jambi, 2025)
Menopause is part of a woman's life process. In Indonesia, women experience menopause on average at the age of 40-50 years. The menopause period is preceded by a decrease in body function in the reproductive organs and changes in menstrual patterns. Menopausal syndrome can be minimized with proper treatment and appropriate screening. Useful information according to what partners need will help them face menopause better. Menopause preparation activities through the use of digital literacy are carried out with health education, lectures, discussions and direct practice as well as random tests on respondents who participate. Participants in this activity consist of KB acceptors and cadres. There are 50 respondents and accompanied by the head of the family planning village and the Aur Kenali sub-district. Providing information about menopause will help women go through menopause better. With screening and consumption of the right foods and vitamins, it will help women go through the climacteric period with a decrease in stress symptoms, somatic symptoms and better mental symptoms. The results of the activity showed an increase in participant knowledge. It is hoped that cadres and participants can use social media as a source of digital literacy more wisely and according to their needs, especially in preparation for menopause.